Dataset of 3D foraminifera to unravel environmental changes in the Baltic Sea entrance over the last 200 years - Choquel, Constance (Lund University, 2023)
Dataset of 3D reconstructions of the foraminifer Elphidium clavatum (marine protist with a calcite shell) acquired at the Beamline BL 47XU, SPring-8 synchrotron facility (Japan). A voxel size of 0.5 µm was used. In total, 124 specimens of Elphidium clavatum were scanned. For each specimen are available: a collection of raw images ("cropped" folder), a collection of binary images ("mask" folder), a 3D reconstruction (STL file), and two snapshot images of the 3D reconstruction. Sediment cores were collected in 2013 during a cruise with R/V Skagerak at Öresund station DV, north of the Island of Ven (55°55.59′ N, 12°42.66′ E). From the sediment core, 16 sediment layers were selected, representing the last 200 years (i.e., roughly the years ~2013, ~2010, ~2005, ~2002, ~1993, ~1986, ~1978, ~1960, ~1939, ~1923, ~1906, ~1890, ~1873, ~1857, ~1840, and ~1807). Between five to ten Elphidium clavatum specimens were selected from each layer. The dataset is part of the study exploring 3D time series of microfossils recording environmental conditions in the Baltic Sea entrance from the period early industrial (the 1800s) to present-day (the 2010s). The size of the dataset is 57 GB. Please contact the main author for further details.

124 specimens of Elphidium clavatum from 16 sediment layers were scanned. For each specimen, the following files are available: a collection of raw images in TIF format ("cropped" folder), a collection of binary images in TIF format ("mask" folder), a 3D reconstruction in STL format, and two snapshot images of the 3D reconstruction in TIF or PNG format. A voxel size of 0.5 µm was used. The data for each specimen is stored in a folder named as follows: DV(sediment depth in cm)-sp(specimen number)-(estimated year), e.g., “DV1-sp2-2013” (sediment depth: 1 cm, specimen 2, estimated year 2013). Examples of suitable software for handling the files include ImageJ and MeshLab.

Total number of files: 69,652 (plus a readme file with documentation)
Total number of folders: 390
Dataset size: 57,1 GB

Dataset med 3D-rekonstruktioner av foraminifären Elphidium clavatum (marin protist med kalcitskal) som förvärvats vid Beamline BL 47XU, SPring-8 synkrotronanläggning (Japan). En voxelstorlek på 0,5 µm användes. Totalt skannades 124 exemplar av Elphidium clavatum. För varje exemplar finns följande filer tillgängliga: en samling råbilder (mappen "cropped"), en samling binära bilder (mappen "mask"), en 3D-rekonstruktion (STL-fil) och två ögonblicksbilder av 3D-rekonstruktionen. Sedimentkärnor samlades in 2013 under en kryssning med R/V Skagerak vid Öresundsstationen DV, norr om ön Ven (55°55,59′ N, 12°42,66′ E). Från sedimentkärnan valdes 16 sedimentlager ut som representerar de senaste 200 åren (dvs. ungefär åren ~2013, ~2010, ~2005, ~2002, ~1993, ~1986, ~1978, ~1960, ~1939, ~1923, ~1906, ~1890, ~1873, ~1857, ~1840 och ~1807). Mellan fem och tio exemplar av Elphidium clavatum valdes ut från varje lager. Datamängden är en del av studien som utforskar 3D-tidsserier av mikrofossil som registrerar miljöförhållanden i Östersjöns inlopp från den tidigindustriella perioden (1800-talet) till nutid (2010-talet). Datasetets storlek är 57 GB. Kontakta huvudförfattaren för ytterligare information.

124 exemplar av Elphidium clavatum från 16 sedimentlager skannades. För varje exemplar finns följande filer tillgängliga: en samling råbilder i TIF-format (mappen "cropped"), en samling binära bilder i TIF-format (mappen "mask"), en 3D-rekonstruktion i STL-format och två ögonblicksbilder av 3D-rekonstruktionen i TIF eller PNG-format. En voxelstorlek på 0,5 µm användes. Data för varje exemplar finns i mappar namngett på följande sätt: DV(sedimentdjup i cm)-sp(exemplarnummer)-(beräknat år), t.ex. ”DV1-sp2-2013” (sedimentdjup: 1 cm, exemplar nummer 2, beräknat år 2013). Exempel på lämpliga program för att öppna filerna inkluderar ImageJ och MeshLab.

Antal filer totalt: 69 652 (plus en readme-fil med dokumentation)
Antal mappar totalt: 390
Datasetets storlek: 57,1 GB
Dataset med 3D-foraminifera för att avslöja miljöförändringar i Östersjöns inlopp under de senaste 200 åren
Keywords: benthic foraminifera; 3D reconstructions; 3D-rekonstruktioner; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geology; Geologi